ТHE CONCEPT OF SOCIALLY RESPONSIBLE MARKETING AS THE BASIS OF RELATIONSHIP MARKETING - Рожко, Віктор (SWorldJournal, 2024)
The paper analyzed and synthesized the scientific works of domestic and foreign scientists, clarified the concept of "socially responsible marketing", which means social obligations undertaken by the owner, managers and employees of the enterprise with th